Analisis Performa Rantai Pasok Kentang di PT Agro Lestari Merbabu Kabupaten Magelang - Ni'mah, Ellisa Hidayatun; Setiyawan, Hery; Nurfadillah, Suryani (Universitas Galuh, 2025)
Supply chain performance analysis in the company's supply chain management aims to measure the ability of the company's supply chain to the various stages and activities in the business process involving the flow of products to consumers, financial flows from consumers and the flow of information related thereto. The purpose of this study was to identify the condition of the potato supply chain and analyze the performance of PT Agro Lestari Merbabu's potato supply chain. This study used descriptive methods for Food Supply Chain Network (FSCN) analysis to identify the condition of the potato supply chain and Supply Chain Operation Reference (SCOR) analysis and pairwise comparisons using Analytical Hierarchy Process (AHP) to determine the performance of the potato supply chain that has not been identified in the FSCN framework. The sampling technique used purposive sampling for company key informants and snowball sampling for supply chain actors, namely distributors, business partners and consumers. The results showed that PT Agro Lestari Merbabu's potato supply chain begins with the upstream subsystem, namely the production facilities provider, PT Agro Lestari Merbabu as the onfarm subsystem and consumers as the downstream subsystem. Supply chain performance attributes used include reliability, responsiveness, flexibility and assets. Currently, supply chain performance of Agro Lestari Merbabu Company’s is 81.98, which is classified as average with the highest weighted score being the planning process (plan).